DESIGN OF ANDROID APPLICATION FOR ABSORPTION REFRIGERATION SYSTEM WITH HEAT SOURCE TEMPERATURE BELOW 2000C - ARYA GUNTARA (NIM : 13113107), REVANDI
The absorption refrigeration system is an alternative refrigeration system that has several advantages over the vapor-compression refrigeration system. An Android application for absorption refrigeration system with case of heat source temperature below 2000C is going to be built through this undergraduate thesis. Furthermore, the absorption refrigeration systems that analyzed under this research includes single effect system, half effect system, series flow double effect system, and parallel flow double effect system. By coding using Android Studio software, the Android application of this absorption refrigeration system was successfully created. This application can calculate the performance of each absorption refrigeration system based on The First and Second Law of Thermodynamics. Together with these calculations, this application can also display tables containing the properties of each state point and graphs that illustrate the effect of variation in operating conditions on COP and exergetic efficiency of the system. Based on the graphs presented in the application, it can be concluded that the increase in the heat source temperature, evaporator temperature, and SHE effectiveness causes the COP to increase. Meanwhile, COP falls as the condenser and absorber temperatures increase. The exergetic efficiency increases as the condenser temperature, absorber temperature, and SHE effectiveness increase. Meanwhile, the exergetic efficiency decreases when there is an increase in evaporator temperature. In the case of a rise in the heat source temperature, the exergetic efficiency increases rapidly to its maximum value and decreases thereafter. It is also concluded that the highest COP is generated by parallel flow double effect system, followed by series flow double effect, single effect, and half effect system. Meanwhile, the highest exergetic efficiency is generated by single effect system. The single effect, half effect, series flow double effect, and parallel flow double effect system are suitable for use in temperature range 80-1100C, 60-800C, 120-1600C, and 120-1800C, respectively.